The persistent instructor: 45 years of Kofi the Good Farmer in Ghana. (1st March 2020) - Blaylock, Jennifer
In 1950, the Gold Coast colonial government published the 52-page pamphlet titled Kofi the Good Farmer. In 1953, it was adapted into a thirteen-minute instructional film of the same name. The film, like the booklet, follows a farmer named Kofi as he demonstrates proper cocoa-farming methods. Depicted as a remote, rural farmer who becomes successful because of his implementation of foreign farming techniques and his acceptance of the colonial government's authority to determine and control the cocoa grading scale, Kofi provides evidence of paternalism and racialist colonial rhetoric in British colonial filmmaking. However, 34 years after the making of Kofi, it was re-shown to rural audiences. Why was a dutiful colonial subject like Kofi instructing cocoa farmers over 30 years after Ghana's independence? And what can his use by the postcolonial state tell us about national governance? This article argues that the persistent use of Kofi by Ghana reveals the entangled relationship between colonialism and nationalism in postcolonial governance. Following the subtle changes that Kofi has undergone in his 45 years of government service, I highlight how government-sponsored films construct their audiences as remote in order to reinforce the power of the state in moments of political uncertainty.